The afterlife of trees - Bartlett, Brian, 1953- (Hugh MacLennan poetry series., 2002)
From "The Afterlife of Trees" /Neither sheep nor cows crisscross our lives as much./Trees dangle apples and nuts for the hungry, throw/shade down for lovers, mark sites for the lost,/and first and last are/utterly themselves,/fuller and finer than any letter or number,/any 7 or T. Their fragmentary afterlife goes on/in a guitar's body and a hockey stick, in the beaked faces/up a totem pole and the stake through a vampire's heart,/in a fragrant cheese-board, a Welsh love-spoon,/a sweat-stained axe handle, a giant green dragonfly suspended from the ceiling with twine,/in the spellbinding shapechanging/behind a glass woodstove-door.